SSR-PCR technology in determining the genetic diversity of the fruits of sweet pepper, Capsicum annuum L., for local and imported samples in Iraq (Journal of the College of Basic Education, 2022)
Genetic variation was studied in 22 local and imported samples collected from local Iraqi market by using Single sequence repeat (SSR-PCR). Six primers set were used in this study. These primers produced 33 bands. Molecular weights of these bands ranged between 100 bp to 1500 bp. The number of polymorphic bands is 24, whereas the number of monomorphic bands is 9. The results of Dendrogram of the studied samples depended on SSR-PCR results by using Jaccard coefficient for genetic similarity was distributed the samples into 10 groups. This Dendrogram revealed a higher similarity between Iraqi/Balad green bell pepper and Iraqi/Yousifia green bell pepper with 1 value. This value is the highest between samples in comparison with lowest values (0.35), which are found in Spanish long green. There are another high values were revealed between Jordanian yellow and red bell pepper with 0.98 value. Also, other high similarity values revealed between and Iraqi/ Souwyera green bell pepper and Italian green bell pepper with 0.94 values. Italian orange bell pepper and Iraqi/ Balad and Yousifia green bell pepper (the two samples in same subgroup) showed similarity with 0.88 values. The Italian and Iranian red bell pepper showed similarity with 0.72 values. The three main groups showed dissimilarity with 0.26 values. The genetic distance between studied samples by using Euclidean coefficient revealed the highest values between Iraqi/Balad and Yousifia green bell pepper with Iranian orange bell pepper with 5.656 values, in comparison with the lowest genetic distance between Jordanian green and yellow bell pepper with 1.0 value. The other samples showed genetic distance between 1 and 5.656.